Analisis Pengaruh E-Commerce dan Word of Mouth Pada Keputusan Pembelian Produk Skincare La Roche Posay by L’oreal (Studi Pada Konsumen di Kota Manado) - Reinette Handayani Mantur, Mercy (Jurnal Etnik: Ekonomi-Teknik, 2023)
Along with the rapid changing of technology and information that is increasing in the current digitalization era, industrial development has also increased significantly, including the beauty industry which tends to affect the modern lifestyle of all levels of society both locally and globally. Currently, consumers have enthusiasm for beauty and skin care products, so it is easier to get the desired product, including consumers in the city of Manado. The internet continues to grow rapidly and affect people's shopping lifestyles, from conventional are now shifting towards a modernization lifestyle. The aim of this study is to determine the effect of E-Commerce and Word of Mouth on the Purchase Decision of La Roche Posay Skincare Products in Manado City.The research method used in this research is quantitative methods. Population in this study is La Roche Posay user in Manado City who bought product through e-commerce like shopee and tokopedia. And the sample in this research using roscoe method, so The sample in this study was 78 respondents. The source of data in this study is primary data.Based on the results of this study, the regression equation is as follows: Y= -0.761 + 0.365 (X1) + 0.625 (X2). As a result of the calculation of the t-test, the E-Commerce variable (X1) partially has a positive effect on the Purchase Decision (Y). This can be seen from the probability that E-Commerce (X1) has a probability value smaller than 0.05, namely = 0.000 and the value of tcount 4.849 > ttable 1.991. The Word of Mouth variable (X2) partially positively affects the purchase decision (Y). This can be seen from the degree of probability level smaller than 0.05, which is 0.000 and the value of tcount 5.244 > ttable 1.991. The results of the F test showed a calculated F value of 85.328 > Ftable 3.117, with a significance of 0.000. Which means that the variables E-Commerce (X1) and Word of Mouth (X2) simultaneously affect on the purchase decision (Y).